2008
DOI: 10.1677/joe-07-0525
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C α modulates liver X receptor α transactivation

Abstract: Liver X receptor a (LXRa), an oxysterol-activated nuclear hormone receptor, regulates the expression of genes involved in lipid and cholesterol homeostasis and inflammation. We show here that transactivation by LXRa in monkey kidney COS-1 (Cos-1) cells is decreased by activation of the protein kinase C (PKC) signaling pathway. In transient co-transfection assays, phorbol myristate acetate (PMA) suppressed LXR-dependent transactivation of LXR-responsive reporter genes or the natural promoter of the human ATP-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Similarly, some reports demonstrated that activation of protein kinase A and protein kinase C decreased LXR␣ target gene expressions (39,41), and our previous report suggested that SIK1 can regulate hepatic lipogenesis by controlling SREBP-1c phosphorylation (26). However, the histone deacetylase Sirt1 has been shown to positively regulate LXR␣ target gene expression (18).…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, some reports demonstrated that activation of protein kinase A and protein kinase C decreased LXR␣ target gene expressions (39,41), and our previous report suggested that SIK1 can regulate hepatic lipogenesis by controlling SREBP-1c phosphorylation (26). However, the histone deacetylase Sirt1 has been shown to positively regulate LXR␣ target gene expression (18).…”
Section: Discussionmentioning
confidence: 75%
“…An increase in the expression of CD11b on THP-1 cells treated with PMA for 2 days was observed by flow cytometric and western blotting analysis while the expression of ABCA1 decreased from day 1 to day 5 (Supplementary Figure  3). PMA is presumed to have reduced the ABCA1 gene expression via PKC activation [29], since PKC was activated with PMA as stated above. Taken together, these results suggest that variously differentiated cells were prepared.…”
Section: Discussionmentioning
confidence: 99%
“…The precise roles of individual PKC isoforms will clearly require analysis of the effect of 22-(R)-HC and 9cRA on the activities of individual members along with the effect of their knockdown or knockout on the various cellular responses. The role of PKCa in the regulation of transactivation of LXRa has been previously investigated though these studies were not in macrophages [Delvecchio and Capone, 2008]. Thus, transactivation by LXR was decreased by activation of PKC in monkey kidney COS-1 cells, human embryonic kidney HEK293 cell line and human hepatocellular carcinoma HepG2 cell line [Delvecchio and Capone, 2008].…”
Section: Discussionmentioning
confidence: 97%